'Kuroneko Banzai' and 'Nimbus Libere' as the examples of anti-American military propaganda - Konstantin Rayhert (Cхід, 2017)
The study analyzes two animated films - Japanese film Kuroneko Banzai released in 1933 and French film Nimbus Libere released in 1944 - as the examples of the anti-American military propaganda that uses famous American cartoon characters. Kuroneko Banzai tells the story of the inhabitants of one Pacific island who are attacked by vicious Mickey Mouse. The inhabitants are saved by the heroes of the Japanese tales (Momotaro, Urashima Taro, Kintaro, Issun-bshi etc.). The film is an example of a national military training which, in one hand, involves the images of Japanese fairy tales characters, that is, appeals to the Japanese national tradition hidden in the Japanese tales and Japanese national symbols (sakura), but, in other hand, it contrasts the Japanese fairy tales characters, which symbolize the Japanese national tradition and connection with ancestors and deities (Kami), with American cartoon character Mickey Mouse who stands as an enemy from the West. The portrayal of such popular character like Mickey Mouse as the enemy is actually aimed at demonization of Mickey Mouse and together with him the entire American culture to oppose it to own traditional Japanese culture portrayed by the fairy tales characters. Nimbus Libere tells the story of such American cartoon characters like Mickey Mouse, Donald Duck, Goofy, Popeye the Sailor and Felix The Cat who bomb France. The film attempts to demonize the Anglo-American allies landed in Normandy to make ordinary Frenchmen not to help the allies.